Socio-hydrological frameworks for adaptive governance: addressing climate uncertainty in South Asia - Anjal Prakash; Ritwick George; Anamika Barua (Frontiers in Water)
In an era of growing climate change impacts, there is an increasing need to grasp the complex connection between human society and hydrological systems. Socio-hydrology, an interdisciplinary area between hydrology, sociology, and economics, provides essential insights to uncover how people's conduct impacts water and climate systems and resources. In this context, this paper looks at modern socio-hydrology advances and what they suggest for creating resistance or insensitivity to climate evolution. By synthesizing numerous theoretical backgrounds, empirical works, and case analyses within the concept of socio-hydrology, this paper tries to show that the socio-hydrological approach can provide insights for decision-making and policy intervention for building resilience at different levels. In the complex landscape of South Asia, where water resources are intricately linked across borders, socio-hydrology emerges as a crucial framework for fostering collaboration and resilience. By recognizing the socio-economic and political dynamics that influence water management, transboundary water issues can be approached holistically. Socio-hydrological principles explain how human behavior, cultural norms, and governance structures intersect with hydrological processes. This understanding enables the development of inclusive policies, equitable agreements, and cooperative strategies for sustainable water use and conflict resolution. In particular, the analysis supports the prospect of integrating socio-hydrological factors by recognizing the social components of water management, including human perception, cognition, behavior, and institutions. This paper examines modern socio-hydrology advances and what they suggest for creating resistance or insensitivity to climate evolution. It also explores potential theoretical frameworks and models like integrated assessment models (IAMs), system dynamic models, agent-based models (ABMs), and scenario planning models in socio-hydrology for planning and risk assessment to help facilitate adaptive governance. We find that socio-hydrology could provide an essential framework for enhancing climate resilience and sustainable water governance in South Asia. Adaptive governance approaches, collaboration amongst key stakeholders, and inclusive strategies are necessary to navigate tricky transboundary water disputes, socio-economic disparities, and the vulnerability of marginalized communities, all problems emblematic of the region. Further research in this field is necessary to harness socio-hydrology's potential in addressing the interconnected challenges climate change poses.